Diversity and Distribution of Spa types among Methicillin Resistant Staphylococcus Aureus Isolated from Humans and Livestock in Kabale District - South Western Uganda - Baguma, Andrew; Musinguzi, Benson; Orikiriza, Patrick; Bazira, Joel (Research square, 2021)
Background: S. aureus is a skin and mucosal bacterial commensal of both humans and animals which has evolved as an important pathogen implicated to cause various infections. High levels of antibiotic use have resulted into multi-drug resistance MRSA, especially among HA-MRSA, CA-and LA - MRSA. Awareness on coexistence and diversity of MRSA clones among humans and household Livestock particularly cattle and swine in our region is limited. We used spa typing method to determine spa diversity, distribution and coexistence in outpatients, household contacts and respective livestock (cattle and swine) in Kabale region, south western Uganda. Methods: This was a cross sectional study by design consisting of outpatients, household contacts and livestock. Outpatients (n =100) colonized with MRSA were traced back to their respective homesteads where household members, domestic cattle, and, swine were tested for S. aureus and subsequently MRSA colonization. High-resolution DNA melting analysis was used to determine spa types among MRSA isolates. Overlap of MRSA isolates among humans and livestock was based on the presence of similar spa types. Results: A total of 3371 S.aureus isolates were collected from outpatients (n =376), household contacts (n = 1531), Cattle (n = 1159) and Swine (n = 305), among which 482 had mecA gene where 27% (100/376) and 8% (123/1531) were outpatients and household contacts respectively while 11% (132/1159) and 42% (127/305) were cattle and swine respectively. Twenty different spa types were identified; t034, t4677, t108, t1451, t9377, t1081, t040, t701, t041, t002, t044, t037,t121, t127, t922, t032, t019, t018, t012 and t030, among which t034 (109/482), t4677 (53/482), t9377 (63/482) and t1081 (53/482) were most prevalent and distributed among human and livestock. All the MRSA isolates were multidrug resistant to antibiotics tested. Conclusion: In Kabale region, there is high diversity of spa types among MRSA. Presence of similar spa types was found circulating among humans and their respective livestock which demonstrates a possible bidirectional transmission. Presence of MDR - MRSA highlights the need for effective prevention and control of MRSA among livestock and in the community using One Health approach.
Keywords: MRSA; Spa types; Diversity; Distribution